Atezolizumab for the First-Line Treatment of Non-small Cell Lung Cancer (NSCLC): Current Status and Future Prospects - Ryu, Rachel; Ward, Kristina E. (Frontiers in Oncology, 2018)
Purpose: Atezolizumab is a programmed death ligand 1 (PDL-1) blocking antibody that was approved for metastatic non-small cell lung cancer (NSCLC) in patients with disease progression. Various studies have been initiated to explore the effectiveness of atezolizumab among different patient cohorts and disease statuses, including as first-line therapy. The purpose of this paper is to identify and summarize the trials that use atezolizumab as a first-line agent in chemotherapy-naïve patients with NSCLC. Methods: A database search was performed on Pubmed, Embase, and Wiley Cochrane Library - Central Register of Controlled Trials to identify clinical trials using atezolizumab as first-line therapy in NSCLC. Additionally, ClinicalTrials.gov and the International Clinical Trials Registry Platform (ICTRP) were searched to identify relevant clinical trials. Conference abstracts from the American Society of Clinical Oncology, the European Society for Medical Oncology, and the American Association for Cancer Research were hand-searched. Any trial in which atezolizumab was used as first-line therapy in chemotherapy-naive patients with NSCLC was included. Results: Fifteen studies were ultimately included, all of which are current and ongoing. Of the 15 studies, 5 have reported results. When given in the first-line setting, atezolizumab had higher rates of objective response, progression-free survival, and overall survival, compared to the second and third-line settings. Among the 15 studies, atezolizumab is used as monotherapy (n=5), in combination with chemotherapy (n=6), in combination with targeted therapy such as bevacizumab (n=1), as neoadjuvant/adjuvant therapy (n=3), in combination with stereotactic body radiation therapy (n=1), and in combination with or following chemoradiation (n=1). Conclusion: Available evidence shows promising safety and efficacy with the use of atezolizumab as first-line therapy in NSCLC. Atezolizumab is currently being studied in a variety of treatment settings. If clinical benefits are shown, atezolizumab may deem to be a useful first-line agent in NSCLC.